AN ANALYSIS ON GRAMMATICAL ERRORS IN WRITING PARAGRAPH BY THE SECOND SEMESTER STUDENTS AT ENGLISH STUDY PROGRAM UNIVERSITAS RIAU - Lia Nurikawati; Eliwarti '; Fakhri Ras (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was conducted to analyse the grammatical errors made by second semester students in writing paragraph at the English Study Program of Universitas Riau. The aim of this study was to find out eight types of common grammatical errors they are Passive Voice, Verb Tense and Form, Subject- Verb Agreement, Word Order, Preposition, Articles, Plurality, and Auxiliary that made by the participants of the study.Writing a paragraph test were administered to twenty seven participants. They were asked to write a paragraph in 90 minutes and based on the three topics provided by the writer. Three raters were involved in checking the grammatical errors on the participants’ paragraph writing. Then, the errors were classified and described. From the analysis, it was obtained that the participants of study made 80 errors. They were errors in terms of Verb Tense and Form (32.50%), Plurality (21.25%) and Subject-Verb Agreement (12.50%). The lowest percentage of errors was in terms of Word Order (5%) and Passive Voice (5%).Thus, it needs more concern on these aspects. Moreover, the other errors are need to be focused as well. It is recommended that other reseachers find the reasons of those comitted errors.Key Words: Error Analysis, Grammatical Errors, Writing Paragraph